The Use of E-Textiles in Ontario Education - Hughes, Janette; Morrison, Laura Jane (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
The purpose of this iterative design-based research study was to determine best practices when using e-textiles for learning in four diverse contexts. We employed a qualitative, ethnographic case study approach, and used interviews, observations, journals, and audiovisual materials in our data collection to explore student engagement with e-textile materials over a two-year period. The data from each iteration were coded using a thematic coding system. Results indicated that collaboration, choice, and making with purpose were the most important factors for student engagement and learning. Importantly, we found that different demographics of students require different supports in the learning process with e-textiles, and that student-driven making is critical when using e-textiles for learning.